Chemotypes and antibacterial activities of Inula viscosa essential oils from Algeria - Abdelkader Ounoughi; Messaoud Ramdani; Takia Lograda; Pierre Chalard; Gilles figueredo (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ounoughi A, Ramdani M, Lograda  T, Chalard P, Figueredo G. 2020. Chemotypes and antibacterial activities of Inula viscosa essential oils from Algeria. Biodiversitas 21: 1504-1517. The aim of this work is to investigate the chemical composition and the antibacterial activities of the essential oils from Inula viscosa (L.) Aiton. Samples were collected in the flowering stage, from different localities in Algeria. The aerial parts of I. viscosa were submitted to a hydro distillation. The chemical composition of the essential oil was analyzed by GC and GC/MS. The antibacterial activity of the essential oils was evaluated using the disc diffusion method against fifteen bacterial species. Fifty-eight compounds representing 98.93 ± 2.03% of the total oil was identified in I. viscosa. It was found that the chemical composition was dominated by the presence of the following major products: polygodial (19.8 ± 16.97%), phytol (12.3 ± 9.77%), fokienol (6.01 ± 3.43%), intermedeol neo (5.09 ± 2.38%), caryophyllene oxide (4.91 ± 3.03%), nerolidol-Z (4.46 ± 5.46%), nerolidol-E (4.24 ± 8.07%) and ?-ionone iso methyl-E (3.72 ± 2.26%). The essential oil of I. viscosa has moderate activity against the bacteria tested. In contrast, the Escherichia coli ATCC 25922, Pseudomonon syringae ATCC 53543 and Enterococcus faecalis ATCC 49452 strains are resistant to I. viscosa essential oils. The phytochemical study of I. viscosa showed that it is rich in terpene compounds, with polygodial and phytol as major components. Three distinct chemotypes are highlighted. The (Polygodial-Intermedeol-neo-Phytol) chemotype of Salah Bey population and two chemotypes with Fokinol-polygodial and Fokinol-phytol. Moderate antibacterial activities of essential oils against the bacteria tested were found.